PENGARUH PADAT TEBAR PADA SISTEM POLIKULTUR TERHADAP PERTUMBUHAN SINTASAN, KONVERSI PAKAN, PRODUKSI UDANG VANNAMEI (Litopenaeusvannamei)DAN BENIH IKAN NILA ( Oreochromis niloticus) - Asli, Wahyu Tri; Malik, Andi Adam; -, Khairuddin; Haruna, Harsani (Jurnal Ilmiah Ecosystem, 2019)
Polyculture is a cultivation method used for the maintenance of many products in one field, polyculture has advantages over monoculture, especially the efficiency of spatial utilization, increased land carrying capacity and increased pond tilapia for pond farmers whose land is less productive. Vanammei shrimp (L. Van) is one of the fishery products that can make foreign exchange for the country and tilapia. The objectives to be achieved in this study were to see the optimal effect of polyculture of vanammei shrimp and tilapia by obtaining a rapid survival rate and growth for 2 months in the pond. The research was carried out for two months from May to June 2018. Traditionally, Tadang Palie village, Cempa sub-district, Pinrang Regency, South Sulawesi Province. The design used was completely randomized (CRD) with 4 treatments and 4 replications. Data were analyzed by ANOVA variance. The results showed that the growth rates of Vanammei shrimp and tilapia were highest in the treatment of Vanammei Shrimp (6.37 grams), B tilapia (8.28 grams) and the survival of vanammei shrimp and the best tilapia obtained in treatment B. (73 , 75%) vanammei shrimp and B tilapia (67.50%) and the best biomass was obtained in plot B (1499) while the best feed convection was obtained in treatment B. (1.22). Polyculture of vanammei shrimp and tilapia gives the best results.